the lenguage and esthetics in desingnig by means of the form (2020)
The world is structured by natural and artificial forms, full of meaning transmited in the language configuration, achieving the understanding by the human being, through the experience and the process of perception. The artificial form, is generated by humans, is set as achievement of object thought and materialized, the language of artificial form includes communication the object to the subject, from simple observation of a conglomeration of pieces to the aesthetic information as subjective factor and the perception of whole as more than the sum of its parts, reflected in both the understanding of the use as a symbol system.